Resistance Training With Partial Blood Flow Restriction in a 99-Year-Old Individual: A Case Report - Scarpelli, Maíra Camargo; Bergamasco, João Guilherme Almeida; Arruda, Estevan A. de Barros; Cook, Summer B.; Libardi, Cleiton Augusto (Frontiers in Sports and Active Living, 2021)
In aging populations for which the use of high loads is contraindicated, low load resistance training associated with blood flow restriction (RT-BFR) is an alternative strategy to induce muscle mass gains. This study investigates the effects of RT-BFR on muscle mass, muscle function, and quality of life of a 99-year-old patient with knee osteoarthritis and advanced muscle mass deterioration. Training protocol consisted of 24 sessions of a unilateral free-weight knee extension exercise associated with partial blood flow restriction through a manometer cuff set at 50% of complete vascular occlusion pressure. We evaluated: cross-sectional area (CSA) and thickness (MT) of the vastus lateralis muscle by ultrasound; function through the Timed Up and Go (TUG) test; and quality of life (QoL) by the WHOQOL-bref, WHOQOL-OLD and WOMAC questionnaires. All tests were performed prior to the training period (Pre) and after the 12th (Mid) and 24th (Post) sessions. Changes were considered significant if higher than 2 times the measurement's coefficient of variation (CV). After 24 sessions, there was an increase of 12% in CSA and 8% in MT. Questionnaires scores and TUG values worsened from Pre to Mid and returned in Post. We consider RT-BFR a viable and effective strategy to promote muscle mass gains in nonagenarians and delay the decline in functionality and QoL associated with aging.